Effects of Frequency of Protein Supplementation on Performance by Beef Calves Grazing Dormant Native Range - G. W. Preedy; J. R. Jaeger; J. W. Waggoner; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2018)
Stocker calves that graze forages before entering a feedlot account for more than 75% of the beef calves raised in the United States each year. A large proportion of those will be calves born in the spring and weaned in the fall. Modest growth rates are expected when the quality of fall and winter forages is poor. Growing calves in confinement systems during fall and winter typically allows for greater average daily gain (ADG) than grazing low-quality forages; however, modest overall costs associated with grazing perennial, dormant forages may be competitive during times when feed prices are relatively high. Providing supplemental protein to beef cows grazing dormant, warm-season, native forages (i.e., ≤ 6% crude protein [CP]) has been demonstrated to increase body condition score (BCS), body weight (BW), improve dry matter digestibility (DMD), and forage dry matter intake (DMI). Furthermore, beef cows grazing low-quality forages and supplemented with protein either daily, every third day, or every sixth day had similar BW and BCS. Reducing the frequency of supplement delivery can reduce labor costs and equipment depreciation without negatively affecting animal performance; however, this practice has variable success when used with growing beef cattle. In previous research, steers supplemented with cottonseed cake 3 times weekly had similar BW gain during winter compared to steers supplemented daily. Conversely, in another study, steers grazing winter range and supplemented with dried distillers grain daily had greater ADG than steers supplemented 3 times weekly. Therefore, the objective of this study was to evaluate the performance of young, lightweight stocker calves grazing dormant, native tallgrass pastures and supplemented protein either daily or 3 times weekly throughout the winter.
Keywords: beef calves; pasture; protein; supplementation frequency